Proceedings of the International Conference on Internet-of-Things Design and Implementation 2021
DOI: 10.1145/3450268.3453525
|View full text |Cite
|
Sign up to set email alerts
|

FaiR-IoT

Abstract: Thanks to the rapid growth in wearable technologies, monitoring complex human context becomes feasible, paving the way to develop human-in-the-loop IoT systems that naturally evolve to adapt to the human and environment state autonomously. Nevertheless, a central challenge in designing such personalized IoT applications arises from human variability. Such variability stems from the fact that different humans exhibit different behaviors when interacting with IoT applications (intra-human variability), the same … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Recent work in the literature targets human-in-the-loop smart heating, ventilation, and air conditioning system (HVAC) while trying to assist human satisfaction [40]. RL has been proposed to adapt the HVAC set-point based on human activity [28]. A human-in-the-loop HVAC system should take the human state and preferences into the computation loop while calculating the HVAC set-point.…”
Section: Application 1: Human-in-the-loop Smart Home-a Thermal Systemmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent work in the literature targets human-in-the-loop smart heating, ventilation, and air conditioning system (HVAC) while trying to assist human satisfaction [40]. RL has been proposed to adapt the HVAC set-point based on human activity [28]. A human-in-the-loop HVAC system should take the human state and preferences into the computation loop while calculating the HVAC set-point.…”
Section: Application 1: Human-in-the-loop Smart Home-a Thermal Systemmentioning
confidence: 99%
“…Simulated Human Model: We model the humans as a heat source with heat flow that depends on the average exhale breath temperature (𝐸𝐵𝑇 ) and the respiratory minute volume (𝑅𝑀𝑉 ) [28]. The 𝑅𝑀𝑉 is the product of the breathing frequency (𝑓 ) and the volume of gas exchanged during the breathing cycle, which is highly dependent on human activity.…”
Section: System Design and Implementationmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, recent research in the human-in-the-loop IoT systems has shown that humans have intrinsic inter-and intra-variation. Hence, we can not have one model-fits-all approach in designing real-time adaptations to improve the human learning [15], [14], [76], [5].…”
Section: Introductionmentioning
confidence: 99%